Komposit Polimer Matriks Tungsten: Tinjauan sebagai Alternatif Timbal untuk Pakaian Pelindung Radiasi Medis - Muhammad Rayhan Santosa; Sovian Aritonang (Rekayasa Material, Manufaktur dan Energi, 2026)
ABSTRACTExposure to ionizing radiation in medical environments particularly from X-ray equipment and radioisotopes—poses health risks to medical personnel. Lead (Pb)-based protective clothing is effective in blocking radiation but has drawbacks such as excessive weight, toxicity, and environmental impact. Therefore, recent research has focused on developing polymer composites with tungsten (W) matrices as lighter and safer alternatives. Based on a review of various studies employing tungsten fillers (W, WO₃, WC, WC-Co) within polymer matrices such as PVA, PDPE, Epoxy, PC, EVA, and PDMS, an increase in filler content has been proven to enhance shielding performance against X-rays and gamma rays. Simulation results indicate that filler concentration has a greater influence than particle size, although nano-sized particles provide advantages under certain conditions. Tungsten-based composites exhibit lightweight, non-toxic, and flexible characteristics. Innovations such as hybrid structures, nano-additives, and advanced fabrication methods (electrospinning, 3D printing) further strengthen the potential of these materials. Therefore, tungsten-based polymer composites are considered strong candidates to replace lead in medical radiation protective clothing, although optimization of filler dispersion, mechanical properties, and production efficiency is still required.